2014
DOI: 10.1597/13-046
|View full text |Cite
|
Sign up to set email alerts
|

Submucous Cleft Palate: A Systematic Review of Surgical Management Based on Perceptual and Instrumental Analysis

Abstract: Objective : Submucous cleft palate (SMCP) is a congenital condition associated with abnormal development of the soft palate musculature. In a proportion of cases, this results in velopharyngeal insufficiency (VPI), the treatment for which includes pharyngeal flap surgery, pharyngoplasty, and palate reconstruction. The aim of this paper is to determine whether there is superiority of one or more types of surgical procedure over the others in improving speech in patients with VPI secondary to SMCP. Methodology :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 68 publications
3
51
0
Order By: Relevance
“…The absence of randomized controlled trials and reliance on cohort or case study methodology is in line with previous systematic reviews and surveys in the area of cleft lip and palate (de Ladeira & Alonso, ; Gilleard et al, ; Karri, ). The retrospective nature of most studies is likely secondary to the complex nature of diagnosis and treatment decision‐making within this population.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The absence of randomized controlled trials and reliance on cohort or case study methodology is in line with previous systematic reviews and surveys in the area of cleft lip and palate (de Ladeira & Alonso, ; Gilleard et al, ; Karri, ). The retrospective nature of most studies is likely secondary to the complex nature of diagnosis and treatment decision‐making within this population.…”
Section: Discussionsupporting
confidence: 67%
“…The absence of randomized controlled trials and reliance on cohort or case study methodology is in line with previous systematic reviews and surveys in the area of cleft lip and palate (de Ladeira & Alonso, 2012;Gilleard et al, 2014;Karri, 2006 (Dixon, Marazita, Beaty, & Murray, 2011;Smyth, 2014;Sommerlad et al, 2004).…”
Section: Study Methodological Considerationssupporting
confidence: 67%
See 1 more Smart Citation
“…Various scoring systems have been developed to quantify speech abnormalities; however, there is great variability between centers in the collection and analysis of data (19). As a result, although perceptual speech assessment is the primary method for diagnosing and assessing VPD, indirect objective methods of evaluation, such as nasometry, can also prove useful; especially combined use of nasometry with nasendoscopy provides objective measures of velopharyngeal function (20). Speech is one of the most important parameters to assess when determining the outcome of cleft palate repair or related velopharyngeal surgeries or speech therapy (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy remains regarding which procedure results in the optimal outcome. The main purpose of either surgery is to improve velopharyngeal function (20). Calis et al reported that both Furlow palatoplasty and the pharyngeal flap procedure combined with intravelar veloplasty are effective in the treatment of SMCP; they also suggested a contribution of pharyngeal flap if the patient has significant signs of hypernasality (3).…”
Section: Discussionmentioning
confidence: 99%